URBANIZATION AS A SOCIAL PROCESS: AN ANALYSIS OF HISTORIOGRAPHY (Scientific journal of the Fergana State University, 2023)
This article analyses the historical and modern, foreign and local research based on a multi-dimensional approach from the point of view of the forms-schemes, main directions and strategies of the “urban society”, formed as a result of the expansion and deepening of urbanization processes